2, 2, 2‐Trifluoroethyl Oxalates in the One‐Pot Parallel Synthesis of Hindered Aliphatic Oxamides (Eur. J. Org. Chem. 12/2016). Issue 12 (April 2016) - Bogolubsky, Andrey V.; Moroz, Yurii S.; Mykhailiuk, Pavel K.; Pipko, Sergey E.; Grishchenko, Alexander V.; Zhemera, Anton V.; Konovets, Anzhelika I.; Doroschuk, Roman A.; Dmytriv, Yurii V.; Zaporozhets, Olga A.; Tolmachev, Andrey
Abstract : The cover picture shows a 2, 2, 2‐trifluoroethyl oxalate derivative utilized by Enamine scientists in a one‐pot parallel synthesis of aliphatic oxamides. The developed procedure provides synthetic and medicinal chemists with a facile route to large collections of compounds bearing the oxamide motif. Details are discussed in the article by Y. S. Moroz, P. K. Mykhailiuk et al. on p.2120 ff . This cover is dedicated to the 25th anniversary of Enamine Ltd.